Transwersalizm z perspektywy pedagogiki społecznej. Integracja wiedzy wywodzonej z dorobku nauk społecznych i humanistycznych dla praktyki działania społecznego = Transversalism from the perspective of social pedagogy. Integration of knowledge derived from social sciences and humanities for the practice of social performance - Żukiewicz, Arkadiusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Social pedagogy is one of pedagogy subdisciplines which in a particular way emphasises its utilitarian character. As a detailed science, it thoroughly develops its theoretical potential and, continuing the work of Helena Radlińska (the pioneer of Polish social pedagogues), nurtures the ideas of the service of humanity and reality. The integration of knowledge representing the output of multiple disciplines and fields of study is one of the constitutive characteristics of social pedagogy.
Keywords: pedagogika społeczna; transwersalizm; nauki społeczne; nauki humanistyczne; działania społeczne